Application of Immunoassays for Rapid Monitor of Carbofuran Residue in Vegetables. Issue 11 (7th October 2019) - Zhao, Yajie; Tan, Guiyu; Wang, Mian; Lin, Huan; He, Lishan; Li, Lingyun; Wang, Baomin
Abstract : Abstract: Carbofuran residue in vegetables is a concern to human health. Direct competitive enzyme‐linked immunosorbent assay (dcELISA) and dipstick immunoassay were developed in the present study. The dcELISA showed a 50% inhibition concentration (IC50 ) and working range of 1.3 and 0.2 to 7.5 ng/mL, respectively, while the cutoff value of dipstick immunoassay was 20 ng/mL. Applying the two immunoassays, we achieved the goal of rapid screening of carbofuran residue in commercial vegetables with a simple sample processing method. Among 46 leek, 39 potato, and 39 sweet potato samples, carbofuran residue was detected in 22% of the leek samples, and two samples exceeded the maximum residue limit of China (0.02 mg/kg). In addition, carbofuran residue was found at less than 2.5 ng/g in one potato and one sweet potato samples. The residual level of carbofuran measured by immunoassays agreed well with those determined by ultra‐performance liquid chromatography tandem mass spectrometry. To ensure food safety and human health, it is greatly necessary and meaningful to monitor carbofuran residue in commercial vegetables. Practical Application: Rapid monitoring of carbofuran residue in vegetables is very necessary and important for consumers, regulatory agencies, and food industry.